Image, Text, Stone Intermedial Perspectives on Graeco-Roman Sculpture - Dietrich, Nikolaus; Fouquet, Johannes (Materiale Textkulturen, 2022)
This book explores the intermediality of image and text in Graeco-Roman sculpture. By studying a wide range of material, from grand sculpture to humble reliefs, scholars from different disciplinary backgrounds explore thematic aspects including the interplay of image and epigram, viewing and 'reading' sculpture in space, the issue of (re-)naming statues,and image and inscription seen from the perspective of social status or gender.